Indigenous Democracy in the Policy-making Process - Tiyan Rahmanul Hakim; Nandang Alamsyah Deliarnoor; Neneng Yani Yuningsih (Universitas Pancasakti Tegal, 2023)
The policy process cannot be separated from democracy because in the policy process there is an aggregation of interests and accommodation of interests, where the existing needs of the community will be tied in one package, namely public opinion. The original village democracy was characterized by deliberation in decision-making and involved gotong royong in all implementations related to joint achievement efforts. Meanwhile, traditional rural democracy has undergone a change towards a decline where the implementation of democracy in independent villages (Village Development Index) has no substance. This paper tries to analyze the Policy Process in the Perspective of Original Village Democracy which changes according to and depends on political culture variables and socio-economic variables. This study uses a qualitative method with purposive sampling in determining the informants and interview techniques, observation and documentation. The rest of the data sources are obtained through literature study of concepts and theories about the policy process and democracy that occurs in the village contained in books and several articles that have been published. The data used by the author are primary data and secondary data.